MicroRNA-302d targets IRF9 to regulate the IFN-induced gene expression in SLE. (May 2017) - Smith, Siobhán; Fernando, Thilini; Wu, Pei Wen; Seo, Jane; Ní Gabhann, Joan; Piskareva, Olga; McCarthy, Eoghan; Howard, Donough; O'Connell, Paul; Conway, Richard; Gallagher, Phil; Molloy, Eamonn; et al.
Abstract: Systemic lupus erythematosus (SLE) is a complex disease targeting multiple organs as a result of overactivation of the type I interferon (IFN) system, a feature currently being targeted by multiple biologic therapies against IFN-α. We have identified an estrogen-regulated microRNA, miR-302d, whose expression is decreased in SLE patient monocytes and identify its target as interferon regulatory factor (IRF)-9, a critical component of the transcriptional complex that regulates expression of interferon-stimulated genes (ISGs). In keeping with the reduced expression of miR-302d in SLE patient monocytes, IRF9 levels were increased, as was expression of a number of ISGs including MX1 and OAS1 . In vivo evaluation revealed that miR-302d protects against pristane-induced inflammation in mice by targeting IRF9 and hence ISG expression. Importantly, patients with enhanced disease activity have markedly reduced expression of miR-302d and enhanced IRF9 and ISG expression, with miR-302d negatively correlating with IFN score. Together these findings identify miR-302d as a key regulator of type I IFN driven gene expression via its ability to target IRF9 and regulate ISG expression, underscoring the importance of non-coding RNA in regulating the IFN pathway in SLE. Highlights: miR-302d regulates IFN driven gene expression by targeting IRF9. miR-302d levels are reduced and correlate negatively with IFN score in SLE patients. IRF9 is a novel target gene of miR-302d. Levels of IRF9 are elevated and correlate with ISG expression in SLE patients. miR-302d administration in vivo reduces IRF9 and ISG expression in response to pristane.